Role of Genetic Recombination in DNA Replication of Bacteriophage Lambda I. Genetic Characterization of the Delta Gene - Barta, K. (1974)
We describe the isolation and genetic characterization of point mutations in gene delta, including a temperature-sensitive mutation (del(206)). Genetic methods enable the extraction of a delta mutation from the triple mutant (del,red,gam) and the construction of new genotypes, including del,red and del,gam double mutants. Tests of plating efficiency indicate gene delta is essential for normal phase growth on the polA host. The possible association of delta in a system involving alpha, beta, and gamma is considered.